2019
DOI: 10.1093/pch/pxz066.101
|View full text |Cite
|
Sign up to set email alerts
|

102 A two-centre survey of caregiver perspectives on opioid use for children’s acute pain management

Abstract: Background: Given the current opioid crisis, caregivers have mounting fears regarding the use of opioid medication in their children. We aimed to determine caregivers' a) willingness to accept, b) reasons for refusing, and c) past experiences with opioids. Methods: A novel electronic survey of caregivers of children aged 4 to 16 years who had an acute musculoskeletal injury and presented to two Canadian paediatric emergency departments (ED) (March to November 2017). Primary outcome was caregiver willingness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Deaths from opioids in the USA and Canada have reached epidemic levels [ 22 , 23 ], and media, third sector, and health service responses have increased the salience of the dangers of non-medical use of opioids [ 24 ]. Due to this, along with the unknown risk of developing opioid use disorders after short-term therapeutic use, families may want to avoid exposure to opioids in a clinical trial regardless of their potential effectiveness; recent empirical work supports this notion and has suggested that less than 50% of caregivers would accept opioids for moderate pain after MSK injury [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deaths from opioids in the USA and Canada have reached epidemic levels [ 22 , 23 ], and media, third sector, and health service responses have increased the salience of the dangers of non-medical use of opioids [ 24 ]. Due to this, along with the unknown risk of developing opioid use disorders after short-term therapeutic use, families may want to avoid exposure to opioids in a clinical trial regardless of their potential effectiveness; recent empirical work supports this notion and has suggested that less than 50% of caregivers would accept opioids for moderate pain after MSK injury [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we propose a novel and innovative design for comparative effectiveness trials which include three treatment options and a patient group who may have a strong aversion to one of the treatment options. This innovative design for clinical trials with more than two arms was motivated by a comparative effectiveness trial of pain medications in the emergency department for pediatric musculoskeletal (MSK) injury where families often have a strong preference to avoid opioids [ 12 , 13 ]. This design could improve both internal and external validity compared to traditional randomized controlled trials and existing preference-informed trial designs.…”
Section: Introductionmentioning
confidence: 99%